Maianthemum mexicanum (Liliaceae) una nueva especie de Durango, México - Garcia-Arevalo, Abel (Instituto de Ecología, A.C., 1992)
Maianthémum mexicanum sp. nov., is described from the températe forest of Southern Durango State. The new species is related to M racemosum (L.) Link, but differs in characteristics of the inflorescence.